Twenty years on: The rationale and use of the clinical cross‐sectional orientation in neuroanatomy. Issue 1 (15th August 2022) - Champney, Thomas H.
Abstract: Twenty years ago, it was noted that with the advent of computed tomography (CT), the orientation of neuroanatomy should change. Radiologists had standardized the clinical cross‐sectional view to indicate an inferior view with posterior at the bottom of the field. This is in contrast with the neuroanatomical cross‐sectional view with posterior at the top of the field. For the past 10 years, the author has taught all of the anatomical disciplines including neuroanatomy to more than 2000 students using only the clinical view. This makes learning easier for the students by keeping all of their cross‐sectional views in the same orientation including clinical, radiological, anatomical, embryological, and neuroanatomical. There have been no adverse effects associated with the use of the clinical orientation and there appears to be no valid reason for maintaining the older, nonclinical orientation in contemporary health‐care education.